Upaya Revitalisasi Pasar Tradisional Melalui Pembenahan Faktor Internal Dan Eksternal Pasar Wage Di Nganjuk - Yucky Ginawanti; Prasetya Tri Mahendra (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2019)
The market Wage Nganjuk is a market that has potential is quite high because of its location, so that it becomes the choice of people to shop at the market. Competition with modern markets, dirty, uncomfortable, and minimal facilities is a weakness that is owned by the traditional market.The purpose of this research is to know the strategies of the market Wage Nganjuk in managing traditional market in Nganjuk Regency Surabaya.The methods used in this study is a qualitative approach using the method.This research uses the theory that is based on the factors that influence the strategy analysis (SWOT) according to the theory of Hunger.Those factors are Strengths, Industry, Opportunities, Threats. data collection Techniques used are interviews, observation.Data analysis techniques using interactive analysis techniques, Miles and Huberman.Research results show that the strategy of Market Wage Nganjuk is still not optimal.That is because the lack of supporting infrastructure means still and parking lot in overcoming bottlenecks, it is still the lack of facilities to accommodate the market traders selling in the street in the market, lack of socialization or guidance on a regular basis to the traders.